Genome-wide survey of HMA gene family and its characterization in wheat (Triticum aestivum) - Zahra, Sadaf; Shaheen, Tayyaba; Qasim, Muhammad; Mahmood-ur-Rahman; Hussain, Momina; Zulfiqar, Sana; Shaukat, Kanval; Mehboob-ur-Rahman (PeerJ, 2023)
Background Abiotic stresses, particularly drought and heavy metal toxicity, have presented a significant risk to long-term agricultural output around the world. Although the heavy-metal-associated domain (HMA) gene family has been widely explored in Arabidopsis and other plants, it has not been thoroughly studied in wheat (Triticum aestivum). This study was proposed to investigate the HMA gene family in wheat. Methods To analyze the phylogenetic relationships, gene structure, gene ontology, and conserved motifs, a comparative study of wheat HMA genes with the Arabidopsis genome was performed. Results A total of 27 T. aestivum proteins belonging to the HMA gene family were identified in this study, with amino acid counts ranging from 262 to 1,071. HMA proteins were found to be grouped into three subgroups in a phylogenetic tree, and closely related proteins in the tree showed the same expression patterns as motifs found in distinct subgroups. Gene structural study elucidated that intron and exon arrangement differed by family. Conclusion As a result, the current work offered important information regarding HMA family genes in the T. aestivum genome, which will be valuable in understanding their putative functions in other wheat species.
Keywords: Bioinformatics; Genome-wide analysis; Heavy metal toxicity; HMA gene family; Phylogenetic analysis